C−X (X = N, O) Cross-Coupling Reactions Catalyzed by Copper-Pincer Bis(N-Heterocyclic Carbene) Complexes - Minnick, Jennifer L.; Domyati, Doaa; Ammons, Rachel; Tahsini, Laleh (Frontiers in Chemistry, 2019)
Over the last two decades, N-heterocyclic carbene (NHC)–copper catalysts have received considerable attention in organic synthesis. Despite the popularity of copper complexes containing monodentate NHC ligands and recent development of poly(NHC) platforms, their application in C–C and C–heteroatom cross-coupling reactions has been limited. Recently, we reported an air-assisted Sonogashira-type cross coupling catalyzed by well-defined cationic copper-pincer bis(NHC) complexes. Herein, we report the application of these complexes in Ullmann-type C–X (X = N, O) coupling of azoles and phenols with aryl halides in a relatively short reaction time. In contrast to other copper(I) catalysts that require an inert atmosphere for an efficient C–X coupling, the employed Cu(I)-pincer bis(NHC) complexes provide good to excellent yields in air. The air-assisted reactivity, unlike that in the Sonogashira reaction, is also affected by the base employed and the reaction time. With Cs2CO3 and K2CO3, the oxygen-generated catalyst is more active than the catalyst formed under argon in a shorter reaction time (12 h). However, the difference in reactivity is compromised after a 24 h reaction with K2CO3. The efficient Cu-pincer NHC/O2/Cs2CO3 system provides great to excellent cross-coupling yields for electronically diverse aryl iodides and imidazole derivatives. The catalyst scope is controlled by a balance between nucleophilicity, coordinating ability, and the steric hindrance of aryl halides and N-/O-nucleophiles.